1985
DOI: 10.1007/bf01024117
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of mosquito repellents inArtemisia vulgaris

Abstract: The mugwortArtemisia vulgaris L. (Compositae: Anthemideae) contains insect repellents which can be released from the plant tissues by combustion. Work was carried out to isolate and identify the repellent compounds. The dried, pulverized whole plants were steam-distilled to give a repellent essential oil which was fractionated by column chromatography. Active fractions were analyzed by capillary GC and by combined GC-MS. A number of compounds, mainly monoterpenoids, were identified. When tested as repellents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
3

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 5 publications
2
59
0
3
Order By: Relevance
“…Park et al (2005) demonstrated that several monoterpenes repelled the mosquito Culex pipiens pallens Coquillett (Diptera: Culicidae) and the nonoxygenated monoterpene a-terpinene is more repellent than the DEET commercial repellent. The mugwort Artemisia vulgaris L. (Asteraceae) also contains volatile insect repellents against the yellow fever mosquito Aedes aegypti (L.) Diptera: Culicidae) (Hwang et al, 1985). Hori (1998) and Bruce et al (2005) found linalool was effective, but the response may vary with species.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al (2005) demonstrated that several monoterpenes repelled the mosquito Culex pipiens pallens Coquillett (Diptera: Culicidae) and the nonoxygenated monoterpene a-terpinene is more repellent than the DEET commercial repellent. The mugwort Artemisia vulgaris L. (Asteraceae) also contains volatile insect repellents against the yellow fever mosquito Aedes aegypti (L.) Diptera: Culicidae) (Hwang et al, 1985). Hori (1998) and Bruce et al (2005) found linalool was effective, but the response may vary with species.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, terpinen-4-ol isolated from Artemisia vulgaris (L.) (Asteraceae) repelled the yellow fever mosquito Aedes aegypti (L.) (Culicidae) (Hwang et al, 1985). Coumarin and thujyl alcohol found in Artemisia abrotanum (L.) (Asteraceae) were shown to repel the tick Ixodes ricinus (L.), (Ixodidae) (Tunón et al, 2006).…”
Section: Original Articlementioning
confidence: 99%
“…Thangam and Kathiresan (1992) stated that smoke from burning various dry materials has been used since early times to deter insects especially mosquitoes. Hwang et al (1985) observed that the bundles of dried Artemisia vulgaris were burned to repel biting insects since it contains insect repellents that can be released from the plant by combustion. The smoke of the leaves of Vitex negundo and Leucas aspera were found more toxic to the filarial vector mosquito, Culex quinquefasciatus than the synthetic mosquito mats which contain 4% d-allethrin (Pandian et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Mosquito coils were traditionally made with finely ground Chrysanthemum cinrariaefolium flowers mixed with coconut husks or sawdust (Chadwick, 1985) and also neem kernels and leaves are burned to repel mosquitoes along with mosquito coils (Konradsen et al, 1997). Plants of terrestrial origin have also been reported to be a source of mosquito repellents (Hwang et al, 1985;Thangam and Kathiresan, 1992). Pandian et al (1989) observed the repellent activity of herbal smoke on the biting activity of Culex quinquefasciatus.…”
Section: Discussionmentioning
confidence: 99%